'I am learning peacefulness': Sylvia Plath's liminal art of (un)living. Issue 1 (2nd January 2017) - McKay, Kathy
ABSTRACT: How much of the "Sylvia Plath" we know is a storied life rather than a real one? Can the two be separated? This is complex given that Plath's final collection Ariel was published twice by husband then daughter. How do we (re)construct Plath as a real person when the narrative around her death is enveloped by presumptions and stereotypes of suicide? This paper explores poems from both versions of Ariel with the idea that, rather than living for her suicide, Plath explored experiences of living in a space in-between wanting to live and wanting to die. This passionate ambivalence is demonstrated in poems such as Tulips, Edge, and Lady Lazarus . This paper will not presume that the poems within Ariel represent her whole life; rather, they represent the story of her life during the time in which they were written, tangible artefacts of her inspiration from 1961 to 1963.